2017
DOI: 10.1175/jcli-d-16-0695.1
|View full text |Cite
|
Sign up to set email alerts
|

Improved Consistency of Climate Projections over Europe after Accounting for Atmospheric Circulation Variability

Abstract: The influence of atmospheric circulation on winter temperature and precipitation trends over Europe in the period 2006–50 is investigated in a 21-member initial condition ensemble from a fully coupled global climate model and in a multimodel framework consisting of 40 different models. Five versions of a dynamical adjustment method based on empirical orthogonal function analysis of sea level pressure are introduced, and their performance in removing the effect of atmospheric circulation on temperature and prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…A limit of these approaches is that accurate present-day analogs may not always be available. For example, in the Mediterranean area in winter, the response of atmospheric circulation to greenhouse forcing does not project on individual present-day modes of internal atmospheric variability [23,28]. Using clustering algorithms does not necessarily address this issue, as global warming can force a change in the structure of weather regimes between the present and the future climate simulations [26,29].…”
Section: Internal Variability Analogsmentioning
confidence: 99%
“…A limit of these approaches is that accurate present-day analogs may not always be available. For example, in the Mediterranean area in winter, the response of atmospheric circulation to greenhouse forcing does not project on individual present-day modes of internal atmospheric variability [23,28]. Using clustering algorithms does not necessarily address this issue, as global warming can force a change in the structure of weather regimes between the present and the future climate simulations [26,29].…”
Section: Internal Variability Analogsmentioning
confidence: 99%
“…There have been attempts to separate out the noise components in climate model ensemble signals. For example, Saffioti et al (2017) showed that the removal of atmospheric circulation variability largely decreases the spread of trends in an initial condition ensemble as well as a multi-model ensemble of GCMs. Since there is no better multi-model ensemble available so far (in terms of sampling different models and members), the CORDEX ensemble can be seen as a first order approximation of the uncertainty in a multi-GCM/RCM ensemble.…”
Section: Composition Of the Cordex Ensemblementioning
confidence: 99%
“…''Dynamical adjustment'' techniques have been developed with the ultimate goal of removing the estimated influence of internal atmospheric circulation variability on target climate variables in the observational record or in models (Wallace et al 2012;Deser et al 2016;Smoliak et al 2015;Saffioti et al 2016). This research followed upon a large suite of earlier studies aiming to understand the relationship between modes of internal atmospheric variability and temperature or precipitation (Wallace et al 1995;Thompson et al 2000;Compo and Sardeshmukh 2010;Foster and Rahmstorf 2011;Iles and Hegerl 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, an improved statistical estimate of the circulation-induced contribution would translate into a higher signal-to-noise ratio in the residual (Smoliak et al 2015). Different dynamical adjustment methods, among them circulation analog techniques (Deser et al 2016;Merrifield et al 2017;Lehner et al 2017) or regression-based approaches (Smoliak et al 2015;Saffioti et al 2016), are different ways to approach the statistical estimation step.…”
Section: Introductionmentioning
confidence: 99%